2006
DOI: 10.1177/0091270006289850
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamic Effects of the Oral DPP‐4 Inhibitor Sitagliptin in Middle‐Aged Obese Subjects

Abstract: Sitagliptin (MK-0431) is an oral, potent, and selective dipeptidyl peptidase-IV (DPP-4) inhibitor developed for the treatment of type 2 diabetes. This multicenter, randomized, double-blind, placebo-controlled study examined the pharmacokinetic and pharmacodynamic effects of sitagliptin in obese subjects. Middle-aged (45-63 years), nondiabetic, obese (body mass index: 30-40 kg/m2) men and women were randomized to sitagliptin 200 mg bid (n = 24) or placebo (n = 8) for 28 days. Steady-state plasma concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 22 publications
0
115
0
1
Order By: Relevance
“…3). Furthermore, in accordance with no preference for Pro, inhibitor analysis using P32/98 (39), sitagliptin (40), and vildagliptin (41), potent inhibitors of human DPP4, demonstrated that neither had an effect on Lys-Ala-MCA hydrolysis by PGN_0756, whereas these compounds completely abrogated the activity of P. gingivalis DPP4 toward Lys-Ala-and Gly-Pro-MCA (Fig. 4).…”
Section: Dipeptide Production In P Gingivalis Wild Type and Kdp136-mentioning
confidence: 68%
“…3). Furthermore, in accordance with no preference for Pro, inhibitor analysis using P32/98 (39), sitagliptin (40), and vildagliptin (41), potent inhibitors of human DPP4, demonstrated that neither had an effect on Lys-Ala-MCA hydrolysis by PGN_0756, whereas these compounds completely abrogated the activity of P. gingivalis DPP4 toward Lys-Ala-and Gly-Pro-MCA (Fig. 4).…”
Section: Dipeptide Production In P Gingivalis Wild Type and Kdp136-mentioning
confidence: 68%
“…ANCOVA models containing creatinine clearance as a continuous or categorical variable and covariates of age, sex, and weight were both used for analysis of pharmacokinetic parameter data. Based on the apparent wide therapeutic index of sitagliptin (2,5,6), an increase in plasma sitagliptin exposure (i.e., AUC 0 -ϱ ) of less than twofold was not considered clinically meaningful.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…45 This results in at least a two-fold increase in post-meal levels of endogenous GLP-1 compared with placebo. [45][46][47] The greatest HbA 1c reductions reported with sitagliptin have been observed when it has been used in combination with metformin in previously OAD-naïve patients (placebo-adjusted reductions of -0.83 and -1.57% for sitagliptin 100mg…”
Section: Sitagliptinmentioning
confidence: 99%